Land cover matters to human well-being - Chao Li (Nature Portfolio, 2021)
Abstract People migrate from rural to urban areas. In the meantime, the benefits of staying in greener areas are also known. People’s preferences might be different by area that is composed of several land types. If so, the effect of particular land cover on human well-being is different spatially. The spatial analysis is required to formulate effective land-use policies. Here we show that urban land, water, and grassland are positively related to human well-being, whereas bare land is negatively associated in Japan. A 1 $${\mathrm{m}}^{2}$$ m 2 increase in the area of urban land per capita in a city is equivalent to an about 346 USD increase in the individual annual income of all the people in the city. Additionally, monetary values of areas of water, crops, and bare land per capita are 102, − 30, and − 268 $$\mathrm{USD}/\mathrm{Capita }{\mathrm{m}}^{2}$$ USD / Capita m 2 . Furthermore, the spatial context matters to the relationship between land cover and human well-being. This paper investigates the monetary values of several land types and their spatial variability, which provides insights to make better usage for land cover.